Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/1747-0080.12494
|View full text |Cite
|
Sign up to set email alerts
|

Development and relative validity of a self‐administered semi‐quantitative drinks frequency questionnaire, validated in a population of university students

Abstract: Aim Drinks can contribute to energy as well as micro‐ and macro‐nutrient intake. Drink‐specific, validated, quick and easy to administer questionnaires are needed to monitor secular trends in beverage consumption for different populations. The aim of the present cross‐sectional study was to develop and validate a drink‐specific questionnaire for the Greek population. Methods A 41‐item semi‐quantitative drinks frequency questionnaire (DFQ) was developed and validated against 7‐day weighed food records, among yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
(104 reference statements)
1
5
0
Order By: Relevance
“…Concerning Na intake of participants, our study agrees with previous research, regarding the lack of validity of self-reported Na intake [75]. According to the results, it appears that the reported intake differed from the measured urinary Na excretion, and this is why measuring urinary Na is considered as the gold standard for estimating Na intake [76,77]. Furthermore, it appears that intensive counseling can reduce the Na intake of hypertensive patients, whereas, on the other hand, simple reporting of the recommendations does not appear to be an adequate intervention inducing significant consumption changes.…”
Section: Discussionsupporting
confidence: 88%
“…Concerning Na intake of participants, our study agrees with previous research, regarding the lack of validity of self-reported Na intake [75]. According to the results, it appears that the reported intake differed from the measured urinary Na excretion, and this is why measuring urinary Na is considered as the gold standard for estimating Na intake [76,77]. Furthermore, it appears that intensive counseling can reduce the Na intake of hypertensive patients, whereas, on the other hand, simple reporting of the recommendations does not appear to be an adequate intervention inducing significant consumption changes.…”
Section: Discussionsupporting
confidence: 88%
“…The authors concluded that the PDQ is a useful screening tool for identifying dietary risk among preschoolers. In another paper, Marakis et al 7 demonstrated moderate/fair validity of a drinks frequency questionnaire (41-items) compared with 7-day weighed food records in a Greek young adult population (n = 59). 7 The authors concluded that the questionnaire is a valid and practical monitoring and surveillance tool for measuring habitual drink intake in adults.…”
Section: Validation Studiesmentioning
confidence: 99%
“…In another paper, Marakis et al 7 demonstrated moderate/fair validity of a drinks frequency questionnaire (41-items) compared with 7-day weighed food records in a Greek young adult population (n = 59). 7 The authors concluded that the questionnaire is a valid and practical monitoring and surveillance tool for measuring habitual drink intake in adults. Han et al, 10 in an additional study in this issue, described the three stage development and validation of a diabetes-related nutrition knowledge questionnaire among a sample of Singaporean adults with type 2 diabetes.…”
Section: Validation Studiesmentioning
confidence: 99%
See 2 more Smart Citations